Visual impairment and mortality in patients with type 2 diabetes - Volkert Siersma; Rasmus Køster-Rasmussen; Christine Bruun; Niels de Fine Olivarius; Audun Brunes (BMJ Open Diabetes Research & Care)
Objective To evaluate whether visual acuity impairment was an independent predictor of mortality in patients with type 2 diabetes.Research design and methods This is a 19-year follow-up of a cohort of 1241 patients newly diagnosed with type 2 diabetes and aged 40 years or over. Visual acuity was assessed by practicing ophthalmologists both at diabetes diagnosis and after 6 years. The logarithmic value of the visual acuity (logMAR) was the exposure. Multivariable Cox regression models were adjusted for multiple potential confounders including cardiovascular disease, and censored for potential mediators, that is, fractures/trauma. Primary outcomes were from national registers: all-cause mortality and diabetes-related mortality.Results Visual impairment at diabetes diagnosis was robustly associated with subsequent 6-year all-cause mortality. Per 1 unit reduced logMAR acuity the incidence rate of all-cause mortality increased with 51% (adjusted HR: 1.51; 95% CI 1.12 to 2.03) and of fractures/trauma with 59% (HR: 1.59; 95% CI 1.18 to 2.15), but visual acuity was not associated with diabetes-related mortality. After censoring for fractures/trauma, visual acuity was still an independent risk factor for all-cause mortality (HR: 1.68; 95% CI 1.23 to 2.30). In contrast, visual acuity 6 years after diabetes diagnosis was not associated with the subsequent 13 years’ incidence of any of the outcomes, as an apparent association with all-cause mortality and diabetes-related mortality was explained by confounding from comorbidity.Conclusions Visual acuity measured by ophthalmologists in patients newly diagnosed with type 2 diabetes was an independent predictor of mortality in the short term.